1987
DOI: 10.1007/bf00328128
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of 130-kd mosquito-larvicidal δ-endotoxin gene of Bacillus thuringiensis var. Israelensis in Escherichia coli

Abstract: Five recombinant E. coli clones exhibiting toxicity to Aedes aegypti larvae were obtained from a library of 800 clones containing XbaI DNA fragments of 110 kb plasmid from B. thuringiensis var. israelensis. All the five clones (pMU 14/258/303/388/679) had the same 3.8-kb insert and encoded a major protein of 130 kDa which was highly toxic to A. aegypti larvae. Three clones (pMU 258/303/388) transcribed the 130 kD a gene in the same direction as that of lac Z promoter of pUC12 vector whereas the transcription o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The recombinant plasmid pMEx-B4A encoding the 130-kDa Bt Cry4A larvicidal protein, which has been reconstructed in the pMEx8 expression vector (Buttcher et al, 1990) under control of the tac promoter together with the cry4B promoter (Angsuthanasombat et al, 1987), was used as a template for the site-directed mutagenesis. Mutant plasmids were generated by a polymerase chain reaction (PCR) using a pair of mutagenic primers ( Table 1) that were purchased from Proligo Inc. (Singapore) and Pfu DNA polymerase, following the procedure of the QuickChange TM Mutagenesis Kit (Stratagene, La Jolla, USA).…”
Section: Construction Of Mutant Toxinsmentioning
confidence: 99%
“…The recombinant plasmid pMEx-B4A encoding the 130-kDa Bt Cry4A larvicidal protein, which has been reconstructed in the pMEx8 expression vector (Buttcher et al, 1990) under control of the tac promoter together with the cry4B promoter (Angsuthanasombat et al, 1987), was used as a template for the site-directed mutagenesis. Mutant plasmids were generated by a polymerase chain reaction (PCR) using a pair of mutagenic primers ( Table 1) that were purchased from Proligo Inc. (Singapore) and Pfu DNA polymerase, following the procedure of the QuickChange TM Mutagenesis Kit (Stratagene, La Jolla, USA).…”
Section: Construction Of Mutant Toxinsmentioning
confidence: 99%
“…The complex crystal is composed of at least three major proteins of approximately 130 kDa, 70 kDa, and 28 kDa. The genes for the 130-kDa and the 28-kDa crystal proteins have been cloned and their nucleotide sequences have been reported (1,25,30,31). These cloning experiments have indicated that the 130-kDa and the 28-kDa B. thuringiensis subsp.…”
mentioning
confidence: 99%
“…Toxin expression, inclusion solubilization, and proteolytic activation The cloned Cry4B toxin (Angsuthanasombat et al, 1987), its non-toxic R158A mutant (Sramala et al, 2001), and the cloned Cry1Aa toxin (a generous gift of Dr. J-L Schwartz, National Research Council of Canada) were over-expressed in E. coli as inclusion bodies upon IPTG (isopropyl-β-D-thiogalactopyranoside) induction at 37 o C. After disruption in a French Press Cell, protoxin inclusions in the crude lysates were obtained by centrifugation, as described earlier (Uawithya et al, 1998). Protein concentrations were determined by using a dye-binding method (BioRad, Hercules, USA), with bovine serum albumin (Sigma, St. Louis, USA) as a standard.…”
Section: Methodsmentioning
confidence: 99%